Reproductive biology of the silver perch leiopotherapon plumbeus in Taal and Sampaloc Lakes South Luzon, Philippines - Denusta, Pastor Jones T.; Garcia, Luis Maria B. (Quezon City Institute Biology, College of Science, University of the Philippines Diliman, 2013)
This study re-evaluated information on the reproductive biology of silver perch Leiopotherapon plumbeus from two lake habitats (Taal and Sampaloc Lakes) in South Luzon, Philippines. Ovarian development of 188 fish specimens from both lakes revealed four oocyte development stages (primary and secondary growth, mature, and post-ovulatory follicle stages), allowing females to be classified into four maturation stages, namely: immature, maturing, mature, and spent. Likewise, the characterization of four stages of spermatogenic cells in the testes (spermatogonia, spermatocytes, spermatids and spermatozoa) allowed for the classification of males into three maturation stages, namely : immature, maturing, or redeveloping and mature. The dominating presence of primary growth and yolked oocytes in mature ovary and the presence of all types of spermatogenic cells in mature testis indicated an asynchronous mode of gonad development, supporting earlier reports of year-round spawning of silver perch. Primary growth and yolked (secondary growth) stage oocytes were present in the ovary during the entire annual ovarian cycle of silver perch from both lakes. In both populations fo fish, primary growth stage oocytes were dominant, followed by the yolked-stage oocytes. this may indicate that silver perch is an iteroparous fish species with indeterminate fecundity, wherby the most advanced oocytes are continually recruited from a pool of younger stage oocyte. These studies provide baseline information on the hormonal-induction of oocyte maturation and spermiation in silver perch and may find application in captive breeding and seed production of this important food fish species.
Thesis (Ph.D. Biology)--University of the Philippines Diliman
Keywords: Silver perch -- Reproduction; Silver perch -- Philippines -- Taal lake (Batangas) -- Reproduction